Pengembangan Buku Ilustrasi Tegodek Dan Tetuntel Sebagai Media Ajar Pada Mata Pelajaran Seni Budaya Di SMP - Babat Nufus Tarenaksa S; Tesa Yustika; Pyo Apriliana Munawarah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This research aims to create a learning media book using illustrations of the Tegodek and Tetuntel folktales. This folktale is one of the Sasak folktales that is quite popular in the Lombok area. The story is included in the fable type of story because the characters who play a role in the story are animals. This research is an R&D study that adapts the ADDIE development model which consists of 5 steps: (1) Analysis; (2) Design; (3) Develop; (4) Implement; (5) Evaluate. The data collection techniques used are observation and testing. The data obtained will be analyzed descriptively quantitatively. Furthermore, the results of this research will be implemented in schools, especially at SMPN 3 PUJUT, Central Lombok, as a development of learning media in the subject of Arts and Culture for class VIII. The objectives are (1) to improve the knowledge and skills of SMPN 3 Pujut students in the field of illustration; (2) to provide insight to SMPN 3 PUJUT students as the younger generation about Lombok regional culture in the form of Tegodek and Tetuntel stories